Dari Cuci Air Hingga Keran Mengalir Cerita Pengelolaan Air di Kampung Tator Kalimantan Timur - Santana, Ricky; Soemarwoto, Rini S.; Rajab, Budi (Jayapangus Press, 2025)
Large-scale development in an undeveloped area unites modern industrial processes with significant capital and small groups of politically vulnerable communities. One-sided encounters in the name of development frequently result in social dynamics such as large-scale migration without adequate regional support. The story of water management in Kampung Tator is one example. Practices like washing water and treating water are intriguing to explore. Although the residents of Kampung Tator now enjoy easy access to clean water, they faced challenges in the village's early days. The dynamics that came up in the past and present resulted in solutions to the collective problems of the three parties, community-company-government, particularly water management. This research aims to ensure the sustainability of water management, through various efforts to protect, preserve, find raw water sources, and educate the community. Data were collected and documented by field observations and informant interviews, and the results were then categorized and sorted according to criteria. Water management in Kampung Tator is viewed from multiple perspectives, one of which is socio-cultural. Based on the research findings, the socio-cultural factors influencing water management in Tator Village are economics, gender, politics, and power. Interviews were also held with representatives from the local government, the Regional Drinking Water Company, and other companies to learn about their perspectives on the sustainability of water management, not only in Kampung Tator but also in East Kutai Regency.